Онтологическое аннотирование информационных ресурсов для оптимизации смыслового поиска - Рябова, Н. В.; Шаламов, М. А. (ХНУРЭ, 2008)
The given work is devoted search of new methods and approaches which would improve process of extraction and information integration. The given work is devoted a problem of working out of the program application realising with the help ontology of the set subject domain the decision of a problem of processing and use of computable values
Keywords: аннотирование информационных ресурсов; оптимизация смыслового поиска